BUILDING AN ONLINE SYSTEM FOR APPOINTMENTS TO MEDICAL SPECIALIST: BUILDING AN ONLINE SYSTEM FOR APPOINTMENTS TO MEDICAL SPECIALIST - Vardeva , Ivelina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
It is done an examination which aim is to support making an e-system for making an appointment to a medicine specialist. It is examined existing web-based technologies applied in similar systems as well as their advantages and disadvantages. For the examination work and for the elaboration are used web-date based and program languages. Developing an online based system gives a possibility for creating flexible applications planning to save time and financial resources for the users when they need to do an appointment as well as the medical specialists for their everyday work. For the first time in Bulgaria that type system has been applied in the private business in few years ago. Its appliance at the medical institutions could reduce the time of waiting up in a queue in front the doctor's cabinet and it could bring a better organization at the medical centers.